Resistance Of The Grounding System In Residential Houses In Preventing The Hazard Of Electric Shock To Humans Using Soil Treatment - AYU FITRIANI; JHONI HIDAYAT; NURMAHENDRA HARAHAP; ERIANSYAH SAPUTRA HASIBUAN; NURHAFNI CAROL; JOEL PANJAITAN; SOFYAN AHWAR SYAHPUTRA (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2026)
Electric shock is a fatal risk in domestic environments that require an effective grounding system. Because high resistance can weaken the protective function, optimization through the use of additives is the main focus of this study. This study evaluates the effect of electrode rod planting depth on moist and dry soil types using a mixture of additives. The method used is the three-point method with planting media in PVC pipes. Test results in this study require improvements in the minimum electrode rod planting of at least 1 meter in the ground and with maximum and effective results it is recommended to be 2.44 meters (8 feet) into the ground. And in dry soil the electrode rod needs to be buried up to 3.5 meters to get a resistance value below 5 Ω according to PUIL standards.